Studi Kasus Break Even Point Pada UMKM Seblak Ceu Yani - Pudholi, Ahmad; Setiyawan; Purba, Nur Annisa Failasuffaiza; Utami, Nurharini Budi; Fachrizal, Muhammad; Nabila, Salsa Is; Apriliyanto, Wahid Hidayah; Purnamasari, Dita; Anjellina, Yessyta Novi; Iswahyudi , Andre (Universitas Pahlawan Tuanku Tambusai, 2025)
Seblak Ceu Yani, a culinary business located in South Cikarang, Bekasi, was founded by Mrs. Yani and her two children in April 2022. Carrying the traditional Sundanese dish, seblak, this business offers a